Barriers in education and professional development of Belgian medical imaging technologists and nurses working in radiotherapy: A qualitative study. Issue 3 (August 2022) - Sousa, F.; Vaandering, A.; Couto, J.G.; Somoano, M.; Van Gestel, D.
Abstract: Introduction: Radiotherapy (RT) professionals are not officially recognised or have formal education in many countries, with RT being often a very short component of a broader programme. This study aims to investigate Belgian stakeholders' perpectives regarding existing barriers and solutions for the education and professional development of Radiation therapists (RTT) which regroups medical imaging technologists (MIT) and nurses working in RT. Methods: Nine experts with vast experience in RT were invited to be interviewed; eight participated (4 heads of the RT departments, 2 school representatives, 2 national society's representatives). A semi-structured questionnaire was used. The first two authors open-coded all interviews using thematic analysis. Results: Five themes and eleven sub-themes were drawn from the analysis. Belgian MIT and nurses in RT perform the same roles, but have different educational backgrounds. The barriers in education and professional development are related to law, education landscape, economics, social-cultural context, politics and professional identity. The main difference between the French and Dutch-speaking parts of the country were at the education level. The proposed solutions included modifying the legislative framework surrounding the RTT profession, setting up financial support, formalizing the educational requirements and increasing professional awareness. Future strategies might include the development of advanced roles and responsibilities. Conclusions: Current law, educational landscape and lack of economic support were the main barriers identified. Except for the educational background, no fundamental differences were found between nurses and MIT in the French and Dutch-speaking parts. Perspectives for both professional groups are linked to future legislative and financial actions, the stakeholders involved and a clear strategic vision. In the upcoming years, increased responsibilities and the creation of a master's degree should be foreseen. Implications for practice: Regulation of RTT profession and education and an increase in RT-specific training must be implemented in Belgium to ensure professional development and optimized treatment delivery.